Long-term efficacy of indicated prevention of depression in non-professional caregivers: randomized controlled trial. Issue 7 (21st October 2014) - Otero, P.; Smit, F.; Cuijpers, P.; Torres, A.; Blanco, V.; Vázquez, F. L.
Abstract : Background: Although depression is a common problem among non-professional caregivers, only one trial has evaluated the efficacy of indicated prevention targeting this population and the long-term efficacy is unknown. The aim of this study was to evaluate the long-term efficacy of a brief intervention for the indicated prevention of depression in a sample of female caregivers. Method: A randomized controlled trial was conducted involving 173 participants (mean age 53.9 years) who were allocated to the intervention ( n  = 89) or the usual-care control group ( n  = 84). Blinded interviewers conducted assessments at 1, 3, 6 and 12 months of follow-up. The main outcome measure was the incidence of major depression and the secondary outcomes were compliance with treatment, depressive symptoms, emotional distress and caregiver burden. Results: At the 12-month follow-up, a lower incidence of depression as evaluated using the Structured Clinical Interview for Axis I Disorders of the DSM-IV was found in the intervention group compared with the control group (10.1% v. 25.0%). The relative risk was 0.40 and statistically significant [χ 2  = 6.68, degrees of freedom = 1, p  = 0.010, 95% confidence interval (CI) 0.20–0.81], and the number needed to treat was 7 (95% CI 4–27). There was a significant delay in the onset of depression in the intervention group ( p  = 0.008). The good complier caregivers had a lower incidence of depression. The intervention effect on depressive symptoms, emotional distress and caregiver burden were maintained for 12 months. Conclusions: This is the first study to demonstrate that a brief problem-solving intervention can prevent the onset of depression among non-professional caregivers over the longer term.